Relation Between Food Consumption and Anemia in Children in Primary School in a Final Disposal Waste Area - Aritonang, Evawany; Siagian, Albiner (Pakistan Journal of Nutrition, 2017)
Background and Objectives: Anemia is a public health problem in Indonesia. Iron deficiency is the most common cause of anemia in infants, preschool students, pregnant mothers, adolescents and the elderly. Therefore, it is time to review the current evidence of the relation between food consumption and anemia in primary school students, particularly in waste disposal areas, in which a high risk of anemia is caused by low income and the inability to purchase food high in iron. Materials and Methods: A cross-sectional study with 52 primary students was used as the sample. The primary data comprised hemoglobin levels, nutrient consumption as energy, protein, iron and vitamin C. Results: The number of anemic students remained high at 32.7%. Student’s consumption of nutrients remained below the "Good" category, in which the energy consumption was 65.4%. Overall, 17.3% of students were at a moderately adequate level, 13.5% were less than adequate and 3.8% showed a deficit. Only 23.1% of the sample demonstrated a "Good" level of protein consumption, 25.0% were at a moderate level of adequacy and 32.7% were less than adequate. Of the students, 19.2% were in the deficit category. Conclusion: There is a significant relation (p<0.05) between energy consumption, protein consumption, iron consumption, vitamin C and anemia.